osué 24,1 - 28 : interpretação socioliterária : a narrativa das tradições dos pais e a resposta simbólica ao pluralismo cultural - Farias, Narciso Neves de (2014)
Among the various aspects of religious studies, the one chosen here can be understood in its function of enabling man to express the meaning to life, founded on a logical system in which a new worldview is constructed to legitimize a determined human reality. This dissertation aims, therefore, to understand the social function of a biblical text as an expression of reality; it aims to understand the type of society behind the text, as well as the historical subject responsible its production. The paper seeks to discover how this historical subject reworked its own traditions before a pluralistic and competing symbolic world, and, finally, how a religious basis to express their vision of society was developed. From this perspective, chapter 24,1-28 of the book of Joshua will be used for the analysis of the society and the praxis of the historical subject which produced their traditions. We have tried to understand the mode of social organization of the people during the post-exilic period of the Persian Empire. By way of theoretical orientation for text analysis, the sociological method for understanding the narrative of Js from 24.1 to 28 was chosen to illustrate the theological necessary to establish the cohesion of popular traditions, and to give new meaning to Yahwist religion in face of the diverse cultures of the religious world of that time. This was possible through the realization of a covenant. The covenant made between Yahweh and the various groups, both those who remained in Judah and those who went into exile, was understood as a proposal to legitimize a new project that would ensure justice and the rights of those families of remainders excluded by the exiles, who were defenders of the social organization implanted in Canaan by the Persian administration. This social organization, created in the interest of the Persian Empire, was consisted of villages, also called father houses, were treated as corporate units. With the arrival of the exiled, this social organization of the province of Judah favored the restoration of the temple and worship, as an expression of the political will of the Persian administration.